2010
DOI: 10.1021/la904179x
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Ablation-Induced Synthesis of SiO2-Capped Noble Metal Nanoparticles in a Single Step

Abstract: Here we describe a simple, powerful technique based on the laser ablation of a target immersed in a water solution of a metal salt. With this method, nanoparticles of different metals and alloys can be processed very quickly. Both the target and the salt solution can be chosen to produce metal nanoparticles of different sizes, surface-oxidized nanoparticles (silica-silver, for example), or even more complex structures to be defined by the researcher on one or more steps because the technique combines the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…Several previous workers have developed NPs of silver, gold, bismuth, etc. through this method and have studied the effects of laser power variation on the size of nanoparticles [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous workers have developed NPs of silver, gold, bismuth, etc. through this method and have studied the effects of laser power variation on the size of nanoparticles [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of silver NP coated with silica we used a novel method consisting on the ablation with laser of a high purity (99.99%) silicon target immersed in an aqueous solution of AgNO 3 (at 125 μM concentration) 43,44 . The target was irradiated for 264 s using the 3 rd harmonic of a Nd:YAG laser (λ=355 nm) with a repetition frequency of 5 kHz and a mean power of 1 W. Large silicon particles produced by splashing during irradiation were removed by filtration with a 200 nm cutoff polyethersulfone membrane (Nalgene®), and stock suspensions of Ag@silica NP were prepared in water at a concentration of ~11 nM, corresponding to 65x10 14 NP L -1 .…”
Section: Preparation and Characterization Of Silica-coated Silver Nanmentioning
confidence: 99%
“…With the above ideas in mind, we aimed to investigate the effect of a new type of silver NP 43,44 , including the associated SPR phenomena, on the growing ability of Escherichia coli cells. The NP are composed of a silver core and a thin shell (1-2nm) of silica glass, and are hereafter referred to as Ag@silica.…”
Section: Introductionmentioning
confidence: 99%
“…There are different pathways for synthesizing nanoparticles (NPs); however, it is a challenge for all of them to improve the control of physical properties of the nanostructures, since their behavior will largely depend on their characteristics (Fojtik et al 1993;Jiménez et al 2004;Pyatenko et al 2004;Popovici et al 2006;Pyatenko et al 2007;Jiménez et al 2008;Cobley et al 2009;Jiménez et al 2010;González-Castillo et al 2015;Ermakov et al 2017). In 2008, Jiménez et al demonstrated a novel hybrid physicalchemical method based on a chemical reaction assisted by laser ablation (Jiménez et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is a fast and simple method to synthesize metal-core/dielectric-shell NPs in one step and in an aqueous medium. This method, assisted laser ablation (ALA), is basically a chemical synthesis (redox) where one of the reactants (silicon) is supplied in nanometer dimensions by laser ablation (Jiménez et al 2010). The laser ablation method is a powerful technique for producing nanostructured materials in different environments (Fojtik et al 1993;Jiménez et al 2004;Pyatenko et al 2004;Popovici et al 2006;Ermakov et al 2017).…”
Section: Introductionmentioning
confidence: 99%